KAJIAN FILSAFAT ILMU: IMPLEMENTASI TEORI ESTETIKA MUSIK AL-FARABI PADA LAGU GALA BUNGA MATAHARI - MOHAMMAD ALAUDIN ALEXUMEIN; Achmad Khudori Sholeh; Rizka Lubaba (LP3M IAI Al-Qolam, 2025)
Research on music in the scope of aesthetics will always be interesting. This study uses a qualitative approach with a data mining method via literature review to analyze the song Gala Bunga Matahari through Al-Farabi's theory of musical aesthetics. The purpose of this study is to link Al-Farabi's aesthetic theory, which emphasizes the importance of harmony and harmony in music, in order to analyze the song in more depth. In the context of the song, the analysis was carried out on the elements of harmony with a mathematical scale, the symbolic meaning in the lyrics that convey the theme of longing and hope for the deceased, and the moral role contained in the lyrics. The results of the study show that Gala Bunga Matahari not only meets the technical criteria of harmonious music in the perspective of Al-Farabi's musical aesthetics, but this song also creates emotional harmony that is in accordance with Al-Farabi's musical aesthetic views, and has elements of music as a social instrument in Al-Farabi's musical approach.